Optimisation of additives on the performance of loess/fly ash-based ceramic membrane supports. (1st September 2022) - Tong, Zhi; Wang, Han; Yang, Xiaoyu; Cui, Shuangke; Zhang, Jianxu
Abstract: Inorganic ceramic membranes have received a lot of attention due to their resistance to acid and alkali corrosion and ease of cleaning and utilisation, however, their high cost has limited their widespread use. To obtain lower-cost ceramic membranes with better performance, in this paper, single-channel tubular ceramic membrane supports were prepared using natural loess and solid waste fly ash as raw materials. This paper firstly investigated the effects of various additives (including carboxymethyl cellulose (CMC), graphite, calcium carbonate, copper oxide, magnesium oxide, and manganese dioxide, ) on the pore size distribution, pure water flux, and flexural strength of the supports to select the appropriate additives; secondly, the response surface methodology was used to determine the amount of each parameter to be added. The results showed that CMC was more viscous and malleable compared to graphite and CaCO3, thus increasing the density and pure water flux of the supports. MnO2 improved both the pure water flux and flexural strength of the supports compared to CuO and MgO. The best sample was obtained when the contents of CMC, MnO2, and kaolinite were 9.85 wt%, 10.62 wt%, and 4.8 wt%, respectively, the best sample obtained exhibited a pure water flux of 4985.52 L·m −2 ·h −1 ·MPa −1 and a flexural strength of 45.4 MPa. The support obtained meets the conditions for the application of porous ceramic carriers and provides a viable pathway for the wide application of low-cost ceramic membrane carriers.